2009
DOI: 10.1177/1468794108099322
|View full text |Cite
|
Sign up to set email alerts
|

Being Fred: big stories, small stories and the accomplishment of a positive ageing identity

Abstract: This article is informed by recent trends in narrative research that focus on the meaning-making actions of those involved in describing the life course. Drawing upon data generated during a series of interactive interviews with a 70-year-old physically active man named Fred, his story is presented to illustrate a strategic model of narrative activity. In particular, using the concepts of 'big stories' and 'small stories' as an analytical framework, we trace Fred's use of two specific identities; being fit and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(83 citation statements)
references
References 28 publications
3
79
0
1
Order By: Relevance
“…In addition, various scholars (e.g. Becker, 1997;Laz, 2003;Phoenix & Sparkes, 2006a, 2009Tulle, 2007) suggest that whilst the body as personal and social is never knowable in unmediated ways, narratives are important because bodily experience is deeply embedded in narrative. Narratives are projected from, and inscribed into the body, and these stories can give us insights into our lived aging bodies and cultures that inscribe our bodies with its meanings of age.…”
mentioning
confidence: 99%
“…In addition, various scholars (e.g. Becker, 1997;Laz, 2003;Phoenix & Sparkes, 2006a, 2009Tulle, 2007) suggest that whilst the body as personal and social is never knowable in unmediated ways, narratives are important because bodily experience is deeply embedded in narrative. Narratives are projected from, and inscribed into the body, and these stories can give us insights into our lived aging bodies and cultures that inscribe our bodies with its meanings of age.…”
mentioning
confidence: 99%
“…For example, Phoenix and Sparkes (2009) showed, in the case of Fred, a healthy 70-year-old man, that his small stories within the context of an interview presented him as a healthy and physically active man, while the master narratives of aging are about physical decline. As in other studies of small stories, Fred was found to occasion countercanonical selves through small stories, snapshots of himself that go against what may be expected of his normative categorization as an "older" man.…”
Section: Applications and Outreachmentioning
confidence: 99%
“…It has been proposed that 'humans are storytelling organisms who, individually and socially, lead storied lives' [20, p. 2]. Hence, narrative plays a key role in the process of human meaning-making and in the structuring of life experiences [21,22]. Van Dijck [11] argues that only when our experiences are transformed into stories do we gain agency of our past.…”
Section: Background and Related Workmentioning
confidence: 99%